Determinan perilaku deteksi dini kanker serviks terhadap implementasi co-testing HPV DNA dan IVA di negara berkembang: Sebuah tinjauan sistematis - Fitri Nuraeny; Dwi Sarwani Sri Rejeki; Siwi Pramatama Mars Wijayanti (Holistik Jurnal Kesehatan, 2026)
Background: Cervical cancer remains a major public health concern in developing countries, where screening coverage is still low. Co-testing HPV DNA and IVA/VIA has the potential to improve early detection; however, its success is influenced by women's behavior in accessing and completing the screening pathway. Purpose: To identify the determinants of early cervical cancer detection behavior among women in developing countries in the context of co-testing HPV DNA and IVA implementation. Method: A systematic literature review based on the PICCO framework was conducted. ework. Articles reviewed included studies on HPV DNA testing and IVA/VIA/visual inspection within a single screening algorithm, either as co-testing, concurrent testing, HPV primary screening followed by VIA triage, or screen–triage–treat. Study quality was assessed using JBI Critical Appraisal Tools, and data were synthesized narratively based on individual, social, healthcare service, economic, and cultural factors. Results: Ten primary studies were analyzed. Dominant determinants included knowledge, risk perception, acceptance of screening methods, stigma, partner/family support, transportation costs, service distance, informal employment, geographic access, follow-up systems, number of visits, HPV DNA result turnaround time, and availability of IVA/VIA triage on the same day. HPV self-sampling, single-visit services, community-based approaches, and active recall systems have the potential to increase uptake and reduce loss to follow-up. Conclusion: Behavioral determinants of early cervical cancer detection in the context of co-testing HPV DNA and IVA are multidimensional. Screening programs in developing countries need to integrate education, community-based approaches, easy service access, rapid triage, and active follow-up to increase participation and screening compliance.   Keywords: Cervical Cancer Screening Behavior; Co-Testing Developing Countries; Early Detection Behavioral Determinants; HPV DNA Testing Uptake; Visual Inspection Acetic Acid.